Teologia como fé inteligente: Aspectos teológico-filosóficos - Renato Westphal, Euler (Vox Scripturae - Revista Teológica Internacional, 2010)
Theology is the expression of the intelligent faith, which initiating at the testimony of the Gospel seeks to contribute with answers to specific contexts of the human life. Science and faith don´t exclude each other, but reason needs references that come from faith. Theology is faith with science. The content of theology itself is the person of Jesus Christ. Here is the true resource and content of the entire theology. Therefore, the theological research is free for the dialogue with all of science, philosophy and society. From this viewpoint we have a clear hermeneutics. The Christological principle of the protestant reformation provides a theological reflection with public relevance and confessional commitment.